Bone Marrow Endothelial Cells Regulate Myelopoiesis in Diabetes Mellitus. Issue 3 (21st July 2020) - Hoyer, Friedrich Felix; Zhang, Xinyi; Coppin, Emilie; Vasamsetti, Sathish Babu; Modugu, Ganesh; Schloss, Maximilian J.; Rohde, David; McAlpine, Cameron S.; Iwamoto, Yoshiko; Libby, Peter; Naxerova, Kamila; Swirski, Filip K.; et al.
Abstract : Background: Diabetes mellitus is a prevalent public health problem that affects about one-third of the US population and leads to serious vascular complications with increased risk for coronary artery disease. How bone marrow hematopoiesis contributes to diabetes mellitus complications is incompletely understood. We investigated the role of bone marrow endothelial cells in diabetic regulation of inflammatory myeloid cell production. Methods: In 3 types of mouse diabetes mellitus, including streptozotocin, high-fat diet, and genetic induction using leptin-receptor-deficient db/db mice, we assayed leukocytes, hematopoietic stem and progenitor cells (HSPC). In addition, we investigated bone marrow endothelial cells with flow cytometry and expression profiling. Results: In diabetes mellitus, we observed enhanced proliferation of HSPC leading to augmented circulating myeloid cell numbers. Analysis of bone marrow niche cells revealed that endothelial cells in diabetic mice expressed less Cxcl12, a retention factor promoting HSPC quiescence. Transcriptome-wide analysis of bone marrow endothelial cells demonstrated enrichment of genes involved in epithelial growth factor receptor (Egfr) signaling in mice with diet-induced diabetes mellitus. To explore whether endothelial Egfr plays a functional role in myelopoiesis, we generated mice with endothelial-specific deletion of Egfr ( Cdh5 Cre Egfr fl/fl ). We found enhanced HSPC proliferation and increased myeloid cell production in Cdh5 Cre Egfr fl/fl mice compared with wild-type mice with diabetes mellitus. Disrupted Egfr signaling in endothelial cells decreased their expression of the HSPC retention factor angiopoietin-1. We tested the functional relevance of these findings for wound healing and atherosclerosis, both implicated in complications of diabetes mellitus. Inflammatory myeloid cells accumulated more in skin wounds of diabetic Cdh5 Cre Egfr fl/fl mice, significantly delaying wound closure. Atherosclerosis was accelerated in Cdh5 Cre Egfr fl/fl mice, leading to larger and more inflamed atherosclerotic lesions in the aorta. Conclusions: In diabetes mellitus, bone marrow endothelial cells participate in the dysregulation of bone marrow hematopoiesis. Diabetes mellitus reduces endothelial production of Cxcl12, a quiescence-promoting niche factor that reduces stem cell proliferation. We describe a previously unknown counterregulatory pathway, in which protective endothelial Egfr signaling curbs HSPC proliferation and myeloid cell production. Abstract : Supplemental Digital Content is available in the text.